Analysis of Human Cloning from the Perspectives of Natural Law, Legal Positivism, and Utilitarianism - Putra, Eduard Awang Maha; Pratama, Febrian Rizki; Mohamed, Muhammad Azimuddin (Lex Journal: Kajian Hukum & Keadilan, 2024)
Today cloning has become “the hottest topic” in biotechnology and biomedical studies. The earliest opening questions about human cloning are: Will human cloning become normative on this planet? This seems to be a very simple question, but it is not enough to answer yes or no, it requires deep thinking. The purpose of this research is to analyze the issue of human cloning from the perspective of natural law, legal positivism, and utilitarianism. This research uses an interdisciplinary approach to explore different perspectives in answering the issue at hand. The results show that from the perspective of natural law, human cloning shows that humans have transcended their nature as creatures created by God and instead want to step over God as the creator of all life. While in the perspective of legal positivism, if cloning is done without going through a legal marriage process and can use eggs and any cells other than sperm from the husband and wife concerned, it is very clear that cloning of humans is contrary to or violates positive law in Indonesia (Health Law and Government Regulation on Reproductive Health). Then in the perspective of utilitarianism, the goal of Utilitarian theory can indeed be achieved because cloning can in fact avoid humans from distress or suffering, but this is only for some individuals because cloning does not provide benefits or happiness in a broad scope or in this case society as a whole, especially the lower middle class.